Analisis Semiotika Representasi Budaya Tionghoa dalam Film Crazy Rich Asians - Tjhing Tjhing; Yasinta Ariati (Jurnal Komunikasi dan Bisnis, 2022)
Film is a mass communication media that cannot be separated from the relationship between film and society. The Crazy Rich Asians movie directed by Jon M.Chu and writer by Kevin Kwan is not onlyfor the entertainment media of the audience but an education that provides insight and experience regarding the touch of history, culture, language, life of people of Chinese descent. For example about the inherent characteristics between the people of "Overseas Chinese" and "Mainland China". This research was conducted to determine the signs or symbols used as cultural representations in the film Crazy Rich Asians. The method used for this research is descriptive qualitative using Christian Metz's mise-en-scene. In the study, researchers used several relevant theories, namely:Intercultural Communication, Face Negotiation Theory, Semiotics, and Representations. Referring to the research objectives, the conclusion of this study is the representation ofculture in the Crazy Rich Asiansfilm is shown through scenes by Rachel Chu and Nick Young in Singapura and the use of language and kinds of customs andfamily culture for generations like the meaning of the choice of red, party of wijayakusuma flower blooms, the reason for making dumplings, the meaning ofa family and the mahjong strategy game. Abstrak Film merupakan media komunikasi massa yang tidak lepas dari hubungan antara film dan masyarakat. Film Crazy Rich Asians yang disutradarai oleh Jon M.Chu dan penulis naskah Kevin Kwan tidak hanya untuk media hiburan penonton namun sarana pendidikan yang memberikan wawasan dan pengalaman mengenai sentuhan sejarah, kebudayaan, bahasa, kehidupan orang-orang keturunan Tionghoa. Penelitian dilakukan untuk mengetahui tanda atau simbol yang digunakan sebagai representasi budaya dalam Film Crazy Rich Asians. Penelitian ini menggunakan metode penelitian kualitatif deskriptif dengan teknik analisis semiotika Christian Metz dengan menggunakan mise-en-scene. Pada penelitian, peneliti menggunakan beberapa teori yang relevan, yaitu : Komunikasi Antarbudaya, Teori Negosiasi Wajah, Semiotika, dan Representasi. Adapun hasil penelitian ini adalah Representasi budaya dalam Film Crazy Rich Asians ditampilkan melalui adegan-adegan oleh Rachel Chu dan Nick Young di Singapura dan penggunaan bahasa serta macam adat dan budaya keluarga yang turun menurun seperti makna pemilihan warna merah, pesta mekar bunga wijayakusuma, pembuatan pangsit, dan arti sebuah keluarga serta permainan mahjong.